2017
DOI: 10.1108/jpmh-03-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Overview of challenges to implementation of good practice in perinatal mental health promotion and management, in universal primary care and community services

Abstract: Lucy Marks is the Chief Executive Officer at Compass Wellbeing CIC, London, UK. AbstractPurpose -The purpose of this paper is to describe some of the barriers and solutions to implementing good practice in perinatal mental health promotion in universal services, and propose some ways forward. Design/methodology/approach -This paper describes the rationale and evidence base for proactive management of perinatal mental health in primary care and community services and good practice recommendations. Thereis consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…The high number of women who associate symptoms of antenatal and postnatal depression with "normal responses" indicates that for pregnant women, at least, the signs and symptoms of mood disorders are often indistinguishable from other typical behaviors and experiences. This seems to be supported by the findings of this study that the cause of mental disorders most often identified during the perinatal period is a factor that is directly related to pregnancy (or becoming a mother) itself [13], [14].…”
Section: Discussionsupporting
confidence: 74%
“…The high number of women who associate symptoms of antenatal and postnatal depression with "normal responses" indicates that for pregnant women, at least, the signs and symptoms of mood disorders are often indistinguishable from other typical behaviors and experiences. This seems to be supported by the findings of this study that the cause of mental disorders most often identified during the perinatal period is a factor that is directly related to pregnancy (or becoming a mother) itself [13], [14].…”
Section: Discussionsupporting
confidence: 74%
“…If screening questions are skimmed over or rushed, they will not generate open discussion. This is supported by (Marks, 2017). There is a risk practitioners aim to 'tick a box' by asking the screening questions, and quickly move onto other agenda items.…”
Section: • During the Past Month Have You Often Been Bothered By Havi...mentioning
confidence: 97%
“…There are limitations of NICE Guidance. There is growing evidence to suggest universal services are struggling to fully implement NICE guidance (Marks, 2017). The NICE guidelines focus almost exclusively on women.…”
Section: Do These Resources Exist In Your Area?mentioning
confidence: 99%